Business Rates Retention and Shale Oil and Gas : Technical consultation on draft regulations to allow the 100% local retention of business rates on shale gas and oil sites.: Technical consultation on draft regulations to allow the 100% local retention of business rates on shale gas and oil sites. (2014) - Unknown
No abstract available